Cronobacter sakazakii and Microbiological Parameters in Dairy Formulas Associated With a Food Alert in Chile - Parra-Flores, Julio; Cerda-Leal, Fabiola; Contreras, Alejandra; Valenzuela-Riffo, Nicole; Rodríguez, Alejandra; Aguirre, Juan (Frontiers in Microbiology, 2018)
The objective of this study was to evaluate the presence of Cronobacter sakazakii and microbiological parameters in dairy products associated with a food alert. Ninety dairy product samples were analyzed, including seven commercial brands and two product types (liquid and powdered) from four countries. Aerobic plate count (APC) and Enterobacteriaceae count were performed according to Chilean standards. Cronobacter spp. and C. sakazakii were identified by polymerase chain reaction real time amplification of rpoB and cgcA genes and the genotype by multilocus sequence typing. Eighty-eight percent of dairy products showed APC higher than the detection limit. Fifty percent of liquid commercial brand samples contained APC: 2.6, 2.3, 1.1, and 2.9 CFU/mL in brands A, C, E, and G, respectively. Results for powdered commercial brands were 3.0, 3.6, and 5.7 CFU/g in brands B, D, and F, respectively. Maximum count (5.7 CFU/g) occurred in brand F dairy product manufactured in Chile. Enterobacteriaceae were found in 55% of the samples, 64% in liquid and 51% in powdered commercial brands. In 50% of brands B, D, and E, samples contained 2.9, 2.8, and 2.7 log CFU/g, respectively. Only liquid commercial brands from the United States had Enterobacteriaceae values between 0.1 and 4.5 CFU/mL. Seventeen suspicious strains were isolated and nine were identified as Enterobacter spp. Only eight suspicious strains from four powdered commercial brands (Chile and Singapore) were confirmed as C. sakazakii by rpoB and cgcA gene amplification and fusA sequencing. C. sakazakii prevalence in the analyzed samples was 8.8%. There were 11% of powdered milk brands that contained APC between 4.0 and 4.7 log CFU/g and 55% of the samples contained Enterobacteriaceae. C. sakazakii was found in dairy products manufactured in Chile and Singapore. On the basis of this information, the Chilean Ministry of Health (RSA) decreed a national and international food alert and recalled all the product batches that resulted positive in the present study from supermarkets and pharmacies.